Algebraic Methodology and Software Technology 13th International Conference, AMAST 2010, Lac-Beauport, QC, Canada, June 23-25, 2010. Revised Selected Papers - Johnson, Michael; aPavlovic, Dusko; aSpringerLink (Online service). (Berlin, Heidelberg Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the 13th International Conference on Algebraic Methodology and Software Technology, AMAST 2010, held in Lac-Beauport, QC, Canada, in June 2010. The 14 revised full papers presented were carefully reviewed and selected from 33 submissions. The papers are organized in 1 invited paper, 10 contributed research papers, and 4 system demonstrations.
Electronic reproduction.
Keywords: Computer science; Software engineering; Logic design; Artificial intelligence; Electronic books